Pre-emptive administration of fibrinogen concentrate contributes to improved prognosis in patients with severe trauma. Issue 1 (2nd December 2016) - Yamamoto, Koji; Yamaguchi, Atsushi; Sawano, Makoto; Matsuda, Masaki; Anan, Masahiro; Inokuchi, Koichi; Sugiyama, Satoru
Abstract : Background: Patients with severe trauma often present with critical coagulopathy, resulting in impaired hemostasis, massive hemorrhage, and a poor survival prognosis. The efficacy of hemostatic resuscitation in correcting coagulopathy and restoring tissue perfusion has not been studied. We assessed a novel approach of pre-emptive administration of fibrinogen concentrate to improve critical coagulopathy in patients with severe trauma. Methods: We retrospectively compared blood transfusion volumes and survival prognosis between three groups of patients with trauma, with an Injury Severity Score (ISS) ≥26 over three consecutive periods: group A, no administration of fibrinogen concentrate; group B, administration of 3 g of fibrinogen concentrate after evaluation of trauma severity and a plasma fibrinogen level <1.5 g/L; group C, pre-emptive administration of 3 g of fibrinogen concentrate immediately on patient arrival based on prehospital information, including high-severity injury or assessed need for massive transfusion before measurement of fibrinogen. Results: ∼56% of patients with an ISS ≥26 and transfused with red blood cell concentrates ≥10 units, had hypofibrinogenemia (fibrinogen <1.5 g/L) on arrival. Patients who received fibrinogen concentrate in group C showed significantly higher fibrinogen levels after treatment with this agent than those in group B (2.41 g/L vs 1.88 g/L; p=0.01). Although no significant difference was observed in blood transfusion volumes between the groups, the 30-day survival of patients in group C (all, and those with an ISS ≥26) was significantly better than in group A (p<0.05). The 48-hour mortality rate in patients with an ISS ≥26 was significantly lower in group C than in group A (8.6% vs 22.9%; p=0.005). Further, among patients with an ISS ≥41, the overall mortality was significantly lower in group C than in group A (20% vs 50%; p=0.02). Conclusion: Pre-emptive administration of fibrinogen concentrate for patients with trauma with critical coagulopathy may contribute to improved survival. Level of evidence: Level IV.